Intrathecal Analgesia and Palliative Care: A Case Study - Salins, Naveen S (Medknow Publications, 2010)
Intrathecal analgesia is an interventional form of pain relief with definite advantages and multiple complications. Administration of intrathecal analgesia needs a good resource setting and expertise. Early complications of intrathecal analgesia can be very distressing and managing these complications will need a high degree of knowledge, technical expertise and level of experience. Pain control alone cannot be the marker of quality in palliative care. A holistic approach may need to be employed that is more person and family oriented.